Carbapenem-resistant Klebsiella pneumoniae colonization and infection is associated with lower overall survival in a cohort of haematopoietic stem-cell transplantation patients: mechanism of resistance and virulence by whole-genome sequencing. Issue 10 (19th October 2021) - Higashino, Hermes Ryoiti; Marchi, Ana Paula; Ruedas Martins, Roberta Cristina; Bubach Carvalho, Laina; Vieira Perdigão Neto, Lauro; Farrel Côrtes, Marina; Nivaldo de Oliveira, Fernando; Tarsia Duarte, Edson Luiz; Guimaraes, Thais; Rossi, Flavia; Ferreira, Aliana M.; Rocha, Vanderson; et al.
Abstract : Carbapenem-resistant Klebsiella pneumoniae (CRK) infections are a growing concern in immunocompromised patients. The aim of the present study was to evaluate the impact of CRK colonization and infection in overall mortality for haematopoietic stem-cell transplant (HSCT) patients. We also aimed to investigate resistance and virulence profiles of CRK isolates and assess their epidemiological and genetic relatedness. Patients in the HSCT unit were screened for colonization with CRK with weekly rectal swab or stool cultures and placed under contact precautions. We defined CRK colonization as positive culture from a swab or stool sample grown in MacConkey agar with meropenem at 1 µg ml −1 . Demographic and clinical data were retrieved from the patients' charts and electronic records. According to resistance mechanisms and pulsed field gel electrophoresis profile, isolates were selected based on whole-genome sequencing (WGS) using MiSeq Illumina. Outcomes were defined as overall mortality (death up to D +100), and infection-related death (within 14 days of infection). We report a retrospective cohort of 569 haematopoietic stem-cell transplant patients with 105 (18.4 %) CRK colonizations and 30 (5.3 %) infections. bla KPC was the most frequent carbapenemase in our cohort with three isolates co-harbouring bla KPC and bla NDM. We found no difference in virulence profiles from the CRK isolates. There were also no significant differences in virulence profiles among colonization and infection isolates regarding genes encoding for type 1 and 3 fimbriae, siderophores, lipopolysaccharide and colibactin. In clonality analysis by PFGE and WGS, isolates were polyclonal and ST340 was the most prevalent. Overall survival at D +100 was 75.4 % in in CRK-colonized ( P =0.02) and 35.7 % in infected patients and significantly lower than non-colonized patients (85.8 %; P <0.001). We found a higher overall mortality associated with colonization and infection; KPC was the main resistance mechanism for carbapenems. The polyclonal distribution of isolates and findings of CRK infection in patients not previously colonized suggest the need to reinforce antibiotic stewardship.